Reduced suppressor cell response to Mycobacterium leprae in lepromatous leprosy. - Sasiain, M D (1989)
We have previously shown that concanavalin A (ConA) induction of suppressor cell activity is impaired in patients with lepromatous leprosy (LL). In this study, we demonstrated that the proportion of cells bearing the Leu8 antigen (associated with suppressor-inducer cells) is low in LL patients and tends to normalize during the erythema nodosum leprosum (ENL) episode. Antigen-induced suppressor cell function was evaluated by a two-stage assay. In the first stage, peripheral blood mononuclear cells (PBMC) were cultured for 5 days either in the presence of gamma-irradiated Mycobacterium leprae or in tissue culture medium as a control. In the second stage, mitomycin C-treated suppressor or control cells were added to phytohemagglutinin (PHA)- or ConA-stimulated autologous PBMC. The results indicate that the ability of M. leprae to induce suppressor activity was lower in LL patients than in patients with tuberculoid (TT) and intermediate clinical (BB, BL, BT) forms and Mycobacterium bovis BCG-immunized normal controls. In ENL patients, the percent suppression was between that of TT and normal individuals. M. leprae-induced suppression was more effective on ConA- than on PHA-triggered T-cell proliferation in all groups. In contrast, normal PBMC cultured for 5 days in RPMI 1640 medium (N-C) and cells from patients with leprosy (TT-C and LL-C) had effects of their own on PHA- or ConA-induced proliferation. LL-C depressed the response to ConA and enhanced PHA-induced proliferation of autologous cells. Conversely, TT-C reduced PHA-induced proliferation and increased the ConA response. Suppression of proliferation could not be overcome with exogenous interleukin-2 and was not related to the induction of the Tac antigen. The abilities of LL, TT, ENL, and normal cells to proliferate upon PHA or ConA stimulus were similar, indicating that the defect in the generation of in vitro suppression by M. leprae in LL patients occurred during the induction period (step 1 of assay).